Epidemiology and successful containment of a carbapenem‐resistant Enterobacteriaceae outbreak in a Southern Italian Transplant Institute. Issue 4 (11th June 2019) - Mularoni, Alessandra; Martucci, Gennaro; Douradinha, Bruno; Campanella, Ornella; Hazen, Benjamin; Medaglia, Alice; Arena, Giuseppe; Gruttadauria, Salvatore; Tuzzolino, Fabio; Arcadipane, Antonio; Gioè, Santi; Luca, Angelo; et al.
Abstract: Introduction: Carbapenem‐resistant enterobacteriaceae (CRE) infections are difficult to treat and pose a serious threat to solid organ transplant (SOT) recipients. At our institute we observed an infection burden in 2012. Methods: In order to contain the spread of CRE infections, we established a taskforce to implement guidelines suggested by the Centers for Disease Control and Prevention (CDC) for this type of outbreak. Here, we describe the epidemiology of the outbreak in our SOT population, and the effectiveness of such interventions, by comparing levels of CRE hospital‐acquired infection (HAI) pre‐ and post‐task force intervention (from January 2009 to December 2012, and from September 2013 to December 2016, respectively) through a linear regression model. Results: In this study, we included 933 patients who underwent a total of 1017 SOT procedures, 286 of whom had a CRE‐positive culture (28.8%), of which 65 (22.7% of CRE positive) developed infection. One‐year mortality post‐SOT was significantly higher in patients with CRE infection. After the taskforce intervention, the CRE HAI rate in SOT showed a significant inverse trend (event rate: −1.28, CI −1.70 to 0.86; P < 0.01). Conclusion: In the paucity of treatment options, the application of CDC measures in our SOT institute contributed significantly to containing CRE infections.